Synthesis and Physicochemical Transformations of Size‐Sorted Graphene Oxide during Simulated Digestion and Its Toxicological Assessment against an In Vitro Model of the Human Intestinal Epithelium. Issue 21 (20th March 2020) - Bitounis, Dimitrios; Parviz, Dorsa; Cao, Xiaoqiong; Amadei, Carlo A.; Vecitis, Chad D.; Sunderland, Elsie M.; Thrall, Brian D.; Fang, Mingliang; Strano, Michael S.; Demokritou, Philip
Abstract: In the last decade, along with the increasing use of graphene oxide (GO) in various applications, there is also considerable interest in understanding its effects on human health. Only a few experimental approaches can simulate common routes of exposure, such as ingestion, due to the inherent complexity of the digestive tract. This study presents the synthesis of size‐sorted GO of sub‐micrometer‐ or micrometer‐sized lateral dimensions, its physicochemical transformations across mouth, gastric, and small intestinal simulated digestions, and its toxicological assessment against a physiologically relevant, in vitro cellular model of the human intestinal epithelium. Results from real‐time characterization of the simulated digestas of the gastrointestinal tract using multi‐angle laser diffraction and field‐emission scanning electron microscopy show that GO agglomerates in the gastric and small intestinal phase. Extensive morphological changes, such as folding, are also observed on GO following simulated digestion. Furthermore, X‐ray photoelectron spectroscopy reveals that GO presents covalently bound N‐containing groups on its surface. It is shown that the GO employed in this study undergoes reduction. Toxicological assessment of the GO small intestinal digesta over 24 h does not point to acute cytotoxicity, and examination of the intestinal epithelium under electron microscopy does not reveal histological alterations. Both sub‐micrometer‐ and micrometer‐sized GO variants elicit a 20% statistically significant increase in reactive oxygen species generation compared to the untreated control after a 6 h exposure. Abstract : Simulated digestion of graphene oxide promotes its agglomeration in the gastrointestinal tract, allows it to sequester digestive enzymes, and leads to its chemical reduction. Subsequent exposure of a tri‐culture human intestinal epithelium model to small intestinal digesta of graphene oxide shows that the digested material can significantly increase intracellular production of reactive oxygen species at both micrometer‐ and sub‐micrometer lateral sizes.